Photothermal CO2 catalysis: From catalyst discovery to reactor design - Sun,W; Cao,XE (Chem Catalysis, 2022)
In this activity, Wei Sun, research-stream professor at Zhejiang University, and Xiangkun Elvis Cao, impact fellow at MIT Climate & Sustainability Consortium, exchange views on academic and industrial considerations on the two vital elements of the advanced technology for photothermal CO2 catalysis, i.e., catalyst discovery and reactor design.